Insulin degludec/liraglutide (IDegLira) was effective across a range of dysglycaemia and body mass index categories in the DUAL V randomized trial - Lingvay, Ildiko (Diabetes Obes Metab, 2017)
This study assessed the efficacy of insulin degludec/liraglutide (IDegLira) vs insulin glargine U100 (IGlar) across categories of baseline glycated haemoglobin (HbA1c; ≤7.5%, >7.5% to ≤8.5% and >8.5%), body mass index (BMI; <30, ≥30 to <35 and ≥35 kg/m(2)) and fasting plasma glucose (FPG; <7.2 and ≥7.2 mmol/L) in patients with type 2 diabetes (T2D) uncontrolled on basal insulin, using post hoc analyses of the DUAL V 26‐week trial. With IDegLira, mean HbA1c was reduced across all baseline HbA1c (1.0%‐2.5%), FPG (1.5%‐1.9%) and BMI categories (1.8%‐1.9%), with significantly greater reductions compared with IGlar U100. For all HbA1c, FPG and BMI categories, IDegLira resulted in weight loss and IGlar U100 in weight gain; hypoglycaemia rates were lower for IDegLira vs IGlar U100. More patients achieved HbA1c <7% with IDegLira than IGlar U100 across all HbA1c (59%‐87% vs 31%‐66%), FPG (71%‐74% vs 40%‐51%) and BMI categories (71%‐73% vs 40%‐54%). IDegLira improved glycaemic control and induced weight loss in patients with T2D previously uncontrolled on basal insulin, across the categories of baseline HbA1c, FPG or BMI that were tested.